ANALISIS KAPASITAS KEBUTUHAN LAHAN PARKIR DI ISTANA GEBANG KOTA BLITAR - Rifky Aldila Primasworo Rifky (Universitas Islam Balitar Blitar, 2023)
Gebang palace museum is one of the tourist attractions in the city of Blitar. Many tourists, both from the city of Blitar and outside the city, visit the museum. Ir Soekarno is the first president of the Republic of Indonesia at this time and lives at the Gebang Palace. The Gebang Palace is located at Jalan Sultan Agung No.59, district, Sananweten Jawa Timur, Blitar City, approximately two kilometers from Bung Karno's grave. The method used in this research is a quantitative method in which the data that has been collected is then grouped and analyzed. This analysis was carried out to determine the need for parking area areas, then data analysis was carried out to determine parking characteristics such as parking time duration, parking volume, parking turnover rate, and parking index (Tamin, 2020), and how the needs or conditions of the Gebang Palace parking lot are 5 years Gebang Palace parking area stands on a land area of ​​approximately 2,100 m2 with a capacity of 60 SRP motorcycles, 48 ​​SRP cars, and 5 SRP buses. by predicting the next 5 years, the number of visitors will be 1922 tourists in 2027 from 915 tourists in 2022 with 103 SRP motorbikes, 48 ​​SRP cars, and 27 SRP buses. cars, and 16 buses.